The Eye Pupil’s Response to Static and Dynamic Illusions of Luminosity and Darkness - Daniele Zavagno; Luca Tommasi; Bruno Laeng (i-Perception, 2017)
Pupil diameters were recorded with an eye-tracker while participants observed cruciform patterns of gray-scale gradients that evoked illusions of enhanced brightness ( glare ) or of enhanced darkness. The illusions were either presented as static images or as dynamic animations which initially appeared as a pattern of filled squares that—in a few seconds—gradually changed into gradients until the patterns were identical to the static ones. Gradients could either converge toward the center, resulting in a central region of enhanced, illusory, brightness or darkness, or oriented toward each side of the screen, resulting in the perception of a peripheral ring of illusory brightness or darkness. It was found that pupil responses to these illusions matched both the direction and intensity of perceived changes in light: Glare stimuli resulted in pupil constrictions, and darkness stimuli evoked dilations of the pupils. A second experiment found that gradients of brightness were most effective in constricting the pupils than isoluminant step-luminance, local, variations in luminance. This set of findings suggest that the eye strategically adjusts to reflect in a predictive manner, given that these brightness illusions only suggest a change in luminance when none has occurred, the content within brightness maps of the visual scene.